Knowledge as contributing factor affecting residents’ support towards a sailing event - Abdullah, Nawal Hanim; Patterson, Ian; Pegg, Shane (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
The aim of this research is to determine whether knowledge in sporting event would have impact upon the residents’ views and support towards the Monsoon Cup event. This study utilized social exchange theory and data where data were collected through one to one in-depth semi-structured interview. A total of 14 individuals from the organizing team and 36 local residents were chosen. A purposive sampling and a snowball sampling method was used to gain data from among the most ingenuous respondents. Residents were selected according to their demographic background (gender, age and length of residency) and socio-economic background (type of occupation and level of education). Thematic content analysis was used to analyse the interviews. The results of this study revealed that with knowledge in sporting event such as water sport, residents would view the overall benefits and costs more positively and support the event. The results also confirmed social exchange theory principles, where knowledge is an exchange element which influences residents’ evaluations of the event as bringing greater benefits than costs. As a reward from the exchange process, residents generally supported the future holding of the Monsoon Cup event.